2017
DOI: 10.1016/j.tvjl.2017.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Novel sequence variants of viral hexon and fibre genes in two dogs with canine adenovirus type 1-associated disease

Abstract: There is little information on sequence variation of canine adenovirus type 1 (CAdV-1), the aetiological agent of infectious canine hepatitis (ICH). This study reports hexon and fibre gene sequence variants of CAdV-1 in a dog with systemic ICH and a dog with the ocular form of the disease ('blue eye') in Northern Italy in 2013. One of the sequence variants matched a CAdV-1 fox sequence previously detected in Italy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…In order to confirm interspecies transmission or to determine if the same virus could be involved further studies such as sequencing of the virus in the affected species should be carried out. Recent studies have found specific areas of the CAdV‐1 genome which could be studied to find sequence variation of the virus (Balboni et al., ). That would help to understand the epidemiology of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…In order to confirm interspecies transmission or to determine if the same virus could be involved further studies such as sequencing of the virus in the affected species should be carried out. Recent studies have found specific areas of the CAdV‐1 genome which could be studied to find sequence variation of the virus (Balboni et al., ). That would help to understand the epidemiology of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…There are two sub-types: CAdV type 1 (CAdV-1) and CAdV type 2 (CAdV-2); CAdV-1 is the etiological agent of infectious canine hepatitis, whereas CAdV-2 causes infectious tracheobronchitis and canine enteritis in domestic dogs (Macartney et al, 1988;Almes et al, 2010). Clinical case reports of CAdV-1 (Headley et al, 2013;Balboni et al, 2017) and CAdV-2 (Hamelin et al, 1986;Spibey and Cavanagh, 1989;Buonavoglia and Martella, 2007) support the hypothesis that CAdV continues to circulate in domestic dogs.…”
Section: Introductionmentioning
confidence: 99%
“…Both wolf viruses showed a deletion of 41 bps compared to CAdV-1 vaccine strain CLL, whose genome was 3-bps larger than that of CAdV-1 strain R1261 (Sira et al, 1987). The hexon gene revealed the same pattern of amino acid (aa) substitutions observed in previously characterised CAdV strains isolated in Italy from two dogs (strains 574-2013-RS and 417-2013-L) and a red fox (strain 113-5 L) (Balboni et al, 2017). Specifically, the aa mutation from asparagine to serine at position 388 was shared by those Italian isolates, the wolf isolate from this study (Wolf/835/2015/FRA) and the recent Italian wolf isolate (Pizzurro et al, 2017), defining a clear distinctive pattern of substitution.…”
Section: Ngs Analysis and Genome Structurementioning
confidence: 68%
“…Nonetheless, re-emergence of adenovirus infections in dogs has been documented worldwide (Decaro et al, 2004;Benetka et al, 2006;Müller et al, 2010;Balboni et al, 2014;Pintore et al, 2016). Recent evidences suggest the role of foxes as reservoir of CAdV-1 (Balboni et al, 2017;Walker et al, 2016a). Red foxes are the most significant free-ranging wild species in Europe and represent a sympatric species with the domestic dogs, thus playing an important role in disease ecology, due to their high population density and intrusive behaviour (Bateman and Fleming, 2012;Gehrt et al, 2010).…”
Section: Introductionmentioning
confidence: 99%